184 Two types of anti-TIGIT antibodies with distinct binding epitope and functional activities. (9th November 2020) - Zhong, Tingting; Pang, Xinghua; Huang, Zhaoliang; Chen, Na; Jin, Xiaoping; Xia, Yu; Wang, Maxwell Zhongmin; Li, Baiyong
Abstract : Background: TIGIT is an inhibitory receptor mainly expressed on natural killer (NK) cells, CD8+ T cells, CD4+ T cells and Treg cells. TIGIT competes with CD226 for binding with CD155. In cancers, CD155 has been reported to up-regulate on tumor cells, and TIGIT was found to increase on TILs. 1 Activation of TIGIT/CD155 pathway would mediate immunosuppression in tumor; while blockade of TIGIT promotes anti-tumor immune response. Methods: AK126 and AK113 are two humanized anti-human TIGIT monoclonal antibodies developed by Akesobio. Binding activity of AK126 and AK113 to human TIGIT, and competitive binding activity with CD155 and CD112, were performed by using ELISA, Fortebio, and FACS assays. Cross-reactivity with cynomolgus monkey TIGIT and epitope binning were also tested by ELISA assay. In-vitro assay to investigate the activity to promote IL-2 secretion was performed in mixed-culture of Jurkat-TIGIT cells and THP-1 cells. Results: AK126 and AK113 could specifically bind to human TIGIT with comparative affinity and effectively blocked the binding of human CD155 and CD112 to human TIGIT. X-ray crystal structure of TIGIT and PVR revealed the C'-C'' loop and FG loop regions of TIGIT are the main PVR interaction regions. 2 The only amino acid residue differences in these regions between human and monkey TIGIT are 70C and 73D. AK126 binds to both human and monkey TIGIT, AK113 binds only to monkey TIGIT. This suggests that these residues are required for AK113 binding to human TIGIT, but not required for AK126. Interestingly, results from cell-based assays indicated that AK126 and AK113 showed significantly different activity to induce IL-2 secretion in mixed-culture of Jurkat-TIGIT cells and THP-1 cells (figure 1 A and B), in which AK126 had a comparable capacity of activity to 22G2, a leading TIGIT mAb developed by another company, to induce IL-2 secretion, while, AK113 showed a significantly higher capacity than 22G2 and AK126. Conclusions: We discovered two distinct types of TIGIT antibodies with differences in both epitope binding and functional activity. The mechanism of action and clinical significance of these antibodies require further investigation. References: Solomon BL, Garrido-Laguna I. TIGIT: a novel immunotherapy target moving from bench to bedside. Cancer Immunol Immunother 2018;67 :1659–1667. Stengel KF, Harden-Bowles K, Yu X, et al. Structure of TIGIT immunoreceptor bound to poliovirus receptor reveals a cell-cell adhesion and signaling mechanism that requires cis-trans receptor clustering. Proc Natl Acad Sci USA 2012;109 :5399–5404.